Quality of COVID-19 information, education and communication materials in India: A content analysis. (June 2023) - Biswas, Soniya; Hense, Sibasis; Kodali, Prakash Babu; Thankappan, Kavumpurathu Raman
Objective: This study examined the characteristics and quality of publicly available COVID-19 information education and communication (IEC) materials in India between March and December 2020. Design: An explanatory sequential mixed-method design was employed to examine the characteristics and quality of 265 purposefully selected IEC materials. Setting: The IEC materials analysed were those published between March and December 2020 on the Ministry of Health and Family Welfare website, Government of India. Methods: A checklist was utilised to examine the quality and characteristics of the materials. Thereafter, qualitative analysis provided insights into the contents of the materials with specific focus on the 'COVID-19 continuum of care'. Results: The majority (73.96%, n = 196) of the selected materials were directed towards the general public and had a focus on prevention (67.55 %, n = 179). Despite COVID-19-associated stigma, only 56 (21.13%) of the materials addressed this issue. However, most (95.47%, n = 253) of the materials adhered to quality standards for contents, readability and aesthetics. This qualitative analysis focused on the contents of selected IEC materials using the concept of 'continuum of care'. The analysis identified three important themes: prevention to early diagnosis and treatment; mitigation of stigma and discrimination surrounding COVID-19; and addressing the infodemic caused by COVID-19. Conclusion: The quality of materials was mostly satisfactory and appropriate to the emergent requirements. Strengthening audience engagement and attractiveness of the materials might enhance readability and actionability. A bottom–up approach to the development of future IEC materials, involving the community might widen the coverage of vulnerable populations in future crisis events.